COVID-19 and the Chinese Christian Community in Britain: Changing Patterns of Belonging and Division. (March 2021) - Huang, Yinxuan; Aune, Kristin; Guest, Mathew
Abstract : This article draws on interview data with Chinese Christian leaders to explore how the coronavirus pandemic is affecting the Chinese Christian church in Britain. Based upon twelve semi-structured interviews conducted with Christian leaders in nine cities, the research identifies the ways in which the COVID-19 outbreak is shaping the dynamics of intragroup and intergroup connectedness within and beyond the Chinese church in Britain. It finds that COVID-19 is playing a significant role in social connectedness. This manifests in three ways: the reconfiguration of a sense of belonging at church, the perception of outreach and evangelism, and the relationship between Chinese Christians from different regional backgrounds. These findings outline that the COVID-19 pandemic is triggering both cohesion and division. On the one hand, the outbreak is functioning as an incubator for a stronger sense of belonging to the church and appears to encourage the church to reach out to seekers and the wider community. On the other hand, the pandemic is also dividing the Chinese church through conflicts in political views and social attitudes. Such conflicts, which are primarily about democratic values and views of China's communist regime, are particularly observable between Mandarin-speaking Christians from mainland Chinese backgrounds and Cantonese-speaking Christians from Hong Kong backgrounds. The article argues that the coronavirus pandemic has initiated deeper reconstruction and reform in the Chinese Christian community in Britain in terms of organisation and mission.